Exploration of Tidal‐Fluvial Interaction in the Columbia River Estuary Using S_TIDE. Issue 9 (17th September 2018) - Pan, Haidong; Lv, Xianqing; Wang, Yingying; Matte, Pascal; Chen, Haibo; Jin, Guangzhen
Abstract: Numerous tidal phenomena, including river tides, internal tides, and tides in ice‐covered bay, are nonstationary, which pose a great challenge for traditional tidal analysis methods. Based on the independent point scheme and cubic spline interpolation, a new approach, namely the enhanced harmonic analysis, is developed to deal with nonstationary tides. A MATLAB toolbox, S_TIDE, developed from the widely used T_TIDE, is used to realize the approach. The efficiency of S_TIDE is validated by analyzing a set of hourly water level observations from stations on the lower Columbia River. In all stations, the hindcast of S_TIDE is more accurate than NS_TIDE that is a powerful nonstationary tidal analysis tool adapted to river tides. The changing mean water level and tidal constituent properties obtained by S_TIDE are similar to those obtained by NS_TIDE, continuous wavelet transform, and empirical mode decomposition and highly consistent with theory on river tides. Moreover, different from NS_TIDE that only can be applied to river tides, enhanced harmonic analysis is free of dynamic content, assuming only known tidal frequencies. Therefore, S_TIDE can be applied to all kinds of nonstationary tides theoretically. Though powerful, S_TIDE also has some limitations: S_TIDE cannot be used for prediction and too many independent points in S_TIDE may induce computational memory overflow and unrealistic results. Plain Language Summary: Based on the independent point scheme and cubic spline interpolation, a new approach, enhanced harmonic analysis, was developed to deal with nonstationary tides. Enhanced harmonic analysis is realized by a MATLAB toolbox, S_TIDE, which is developed from the widely used T_TIDE. S_TIDE assumes only known tidal frequencies and theoretically can be applied to all kinds of nonstationary tides and stationary tides. In this study, S_TIDE is applied to analyzing records of river rides that is one of the simplest kinds of nonstationary tides for which ample data are available. The method is compared with other methods to show its efficiency. Key Points: A MATLAB toolbox, S_TIDE, is used to realize enhanced harmonic analysis (EHA) for nonstationary tides S_TIDE can separate oscillations in MWL, amplitudes, and phases on different time scales within a given frequency band using different number of IPs For D4 constituents, not only the time variations but also the along‐channel variations are dominated by river flow